221k views
0 votes
Please help thank you

Please help thank you-example-1
User Calculator
by
3.8k points

2 Answers

3 votes

Answer:

C

Explanation:

User Staven
by
4.3k points
0 votes

Answer:

C

Explanation:

Given the 2 equations

6x + 2y = 8 → (1)

12x + y = 22 → (2)

Multiplying (2) by - 2 and adding to (1) will eliminate the y- term

- 24x - 2y = - 44 → (3)

Add (1) and (3) term by term, thus eliminating y

- 18x = - 36 ( divide both sides by - 18 )

x = 2

Substitute x = 2 into either of the 2 equations and solve for y

Substituting into (1)

6(2) + 2y = 8

12 + 2y = 8 ( subtract 12 from both sides )

2y = - 4 ( divide both sides by 2 )

y = - 2

Solution is (2, - 2 ) → C

User Pkolodziej
by
4.8k points